Use of successional sowing in evaluating cowpea (Vigna unguiculata) adaptation to drought in the Sudan savannah zone. 2. Responseof reproductive traits - Muleba, N.; Mwanke, M.; Drabo, I. (Cambridge University Press, 1991)
Two sets of experiments on cowpea sowing date were conducted in 1983–85 at Ouagadougou, Burkina Faso. One set tested six daylength-insensitive (DI) cultivars and the other compared four or five daylength-sensitive (DS) cultivars with one or two DI cultivars as controls. Sowing after inadequate rainfall, particularly when followed by drought stress, impeded seedling establishment and growth. Severe drought stress during the reproductive growth stages and prolonged drought stress throughout the crop season adversely affected flowering, flowering and subsequent yield. Cultivar differences in ability to withstand drought damage were observed. The ability of cultivars to (i) branch profusely, to compensate for stands lost by drought during seedling growth and (ii) flower at such a time that pod set and fill coincide with favourable climatic conditions appears to be a prerequisite for satisfactory adaptation to the Sudan savannah zone of semi-arid West Africa. Daylength-sensitivity and early maturity per se were inadequate to prevent yield losses under drought conditions.